Contemporary Studies on Suburban (Indonesia) Today: Critique on Classical-Neoclassical Regional Economics Based Institutional Economics Perspectives - Pitri Yandri; D.S. Priyarsono; Akhmad Fauzi; Arya Hadi Dharmawan (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2018)
The current trend shows that the growth of suburban area is increasingly massif, both its total areas as well as quantity. However, the phenomenon is not followed with the attention of researchers to conduct the study on it. Even if there is, their attention escape on an important approach in the analysis. Their analysis rests on old theories which assume that the space planning and land just triggered by the company's and household’s behavior. Nonetheless, the fact remains that land use planning involves complex functions of institution. Therefore, this brief article reports the results of a literature review about the condition of suburban areas in Indonesia. The approach is conducted by critical review using institutional analysis to elaborate classical and neoclassical regional economic theories, as well as comparing and synthesizing the literature. To sharpen the argument, I also present the relevant descriptive data. Through institutional perspective, I argue that the real question of land use planning and its development in the suburbs exists beyond land and infrastructure issues.